Self-criticisms toward a socially responsible science in the field of management - Jesús de Frutos-Belizón; Fernando Martín Alcázar; Gonzalo Sánchez-Gardey (BRQ Business Research Quarterly, 2024)
Management scholarship should be placed in a unique position to develop relevant scientific knowledge because business and management organizations are deeply involved in most global challenges. However, different critical voices have recently been raised in essays and editorials, and reports have questioned research in the management field, identifying multiple deficiencies that can limit the growth of a relatively young field. Based on an analysis of published criticisms of management research, we would like to shed light on the current state of management research and identify some limitations that should be considered and should guide the growth of this field of knowledge. This work offers guidance on the main problems of the discipline that should be addressed to encourage the transformation of management research to meet both scientific rigor and social relevance. The article ends with a discussion and a call to action for directing research toward the possibility and necessity of reinforcing "responsible research" in the management field.
Keywords: M00; M10; 650; Management field; management research; Valley of Death; academic reward system; socially responsible science